ZnO:Al Grown by Sputtering from Two Different Target Sources: A Comparison Study - Abdalla A. Alnajjar (Advances in Condensed Matter Physics)
Al-doped ZnO thin films were deposited from two different targets. Ceramic targets were used in RF magnetron sputtering, whereas pulsed magnetron sputtering was used to grow films from powder targets. ZnO:Al films with different thicknesses were sputtered directly on soda-lime glass substrates. The film thickness was in the 0.04–2.0 μm range. The microstructure, such as the grain size and the texture, of the two differently grown ZnO:Al transparent conductive oxide films of different thickness, was studied using X-ray diffraction θ/2θ scans. The optical properties, such as the transmittance and reflectance, were measured using a UV-Vis-NIR spectrometer. Further, the sheet resistance, resistivity, carrier concentration, and Hall mobility of these ZnO:Al thin films were measured as a function of film thickness. These results obtained from the two different deposition techniques were compared and contrasted.